Lower limb kinematics during the swing phase in patients with knee osteoarthritis measured using an inertial sensor - Tanimoto, Kenji; Takahashi, Makoto; Tokuda, Kazuki; Sawada, Tomonori; Anan, Masaya; Shinkoda, Koichi (Gait & posture, 2017)
•We studied shank angular velocity during swing phase in knee osteoarthritis patients.•Worse knee score was correlated with decreased angular velocity.•Worse knee score was correlated with increased variability of angular velocity.•Worse knee score was correlated with more random variability of angular velocity.•Control of swing limb is affected by degree of disability due to knee osteoarthritis. During gait, the swing limb requires flexible control to adapt to ever changing environmental circumstances. However, few studies have focused on the mechanics of swing limb control in patients with knee osteoarthritis (OA). Investigating the variability of swing limb kinematics, which can be represented by variables such as the peak shank angular velocity during the swing phase obtained from an inertial sensor, provides insights into the adaptability of swing limb control. The purpose of this study was to investigate how patients with knee OA control the swing limb and whether the degree of impairment and disability due to knee OA affects swing limb control. Twelve subjects diagnosed with knee OA and 11 healthy control subjects participated in this study. Subjects walked on a treadmill for 10min. The mean, coefficient of variation, and fractal scaling exponent α of the peak shank angular velocity during the swing phase were calculated. There were no significant differences between the groups for any of the kinematic parameters. The Knee Injury and Osteoarthritis Outcome Score (KOOS) activities of daily living (ADL) subsection correlated with the coefficient of variation (r=−0.677, p=0.016) and the scaling exponent α (r=0.604, p=0.037) of the peak shank angular velocity. Control of the swing limb was associated with the degree of impairment and disability. Larger and more random variability of peak shank angular velocity may indicate decreased ADL ability in patients with knee OA.